)(Study on the Effects Process on Tannin and Phytic Acid Content in Taro (Colocasia esculenta (L) Schott) - M Maman Rohama; Adriana Wahyu Rahmani; Faisal Anwar; Hadi Riyadi; Solechan - (Warta Industri Hasil Pertanian, 1993)
A research on the effect of process on tannin and phytic acid content of taro corm has been conduced.The study was done on fresh,boiled,steamed and roasted taro corm and also taro flour.The result showed that uncooked taro contained 750.5 mg of tannin and 374 mg of phytic acid per 100 gr.Boiling treatment showed the decrease of tannin of 50.17% and the decrese of phytic acid of 13.57%.The streaming treatment resulted in the decrease of tannin of 49.90%and the decreaseof phytic acid of 16.30%.Roasting treatment showed of tannin of 53.63% and phytic acid 51.11% and flour treatment showed the decrease of 35.31%tannin and 64.37%phytic acid.